Health-seeking behavior in dengue hemorrhagic fever in Primary Health Care - Astuti, Fardhiasih Dwi; Artanti, Galuh; Rokhmayanti, Rokhmayanti; Hastuti, Siti Kurnia Widi (Jurnal Cakrawala Promkes, 2025)
Dengue hemorrhagic fever poses a significant public health challenge in tropical and subtropical regions. In 2022, Bantul Regency recorded 957 cases of dengue fever. This study aims to describe the practices and factors that influence health-seeking behavior among people at the Kasihan I Community Health Center in Bantul Regency. Method: This study employs a descriptive quantitative approach. The data were analyzed both descriptively and quantitatively, and the results are presented in percentage form. Results: 52.6% of respondents visited a doctor when symptoms appeared. Sixty-nine point three percent of respondents believed the fever symptoms they were experiencing were due to the common cold. 94% of respondents visited a doctor when they had dengue fever. 37.8% of respondents visited a health facility on the day they first experienced symptoms. 60.4% of respondents visited the health center most often. 61.7% of respondents had a blood test on the third day after the fever appeared. 71.1% of respondents had sufficient knowledge about dengue fever. 77.9% of respondents had a fair attitude towards dengue fever. 93% of respondents rated the availability of health services as available. 90.1% of respondents considered the cost and distance of health services to be affordable. 92.4% of respondents rated access to health services as easy. Conclusion: Most respondents consulted a doctor for dengue fever symptoms, often mistaking them for a cold. They primarily visited primary healthcare facilities, with blood tests usually done on the third day of fever. Overall, respondents had adequate knowledge and positive attitudes about dengue, along with good access to affordable healthcare services.